2007
DOI: 10.1007/s10858-007-9212-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alignment tensors generated for native tRNAVal using magnetic fields and liquid crystalline media

Abstract: SummaryResidual dipolar couplings (RDCs) complement standard NOE distance and J-coupling torsion angle data to improve the local and global structure of biomolecules in solution. One powerful application of RDCs is for domain orientation studies, which are especially valuable for structural studies of nucleic acids, where the local structure of a double helix is readily modeled and the orientations of the helical domains can then be determined from RDC data. However, RDCs obtained from only one alignment media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Compared to values reported for proteins, these scalar products suggest fairly correlated datasets but for comparison, aligning tRNA in phospholipid bicelles, negatively charged bicelles, fd bacteriophage or C 8 E 5 /octanol mixtures leads to at best, a scalar product of 0.87 as compared to Pf1 phage 58 .…”
Section: Resultsmentioning
confidence: 63%
“…Compared to values reported for proteins, these scalar products suggest fairly correlated datasets but for comparison, aligning tRNA in phospholipid bicelles, negatively charged bicelles, fd bacteriophage or C 8 E 5 /octanol mixtures leads to at best, a scalar product of 0.87 as compared to Pf1 phage 58 .…”
Section: Resultsmentioning
confidence: 63%
“…A potential solution to this problem is to measure RDCs in two or more different alignment media that result in different alignment tensors [24]. However, in practice this has not been achieved because alignment media tend to sterically and electrostatically align nucleic acids with their longest helical axis along the z- component of the alignment tensor [25]. Although very few RNAs have been analyzed in this way, Pardi and coworkers showed that the 6 most commonly used alignment media resulted in very similar alignment tensors for tRNA Val [25], and thus do not solve the RDC degeneracy problem.…”
Section: Introductionmentioning
confidence: 99%
“…They arise in the presence of partial molecular orientation, which can be achieved by interactions with alignment media surrounding the molecule (Tolman et al, 1995; Tjandra and Bax, 1997; Hansen et al, 1998; Losonczi and Prestegard, 1998; Ramirez and Bax, 1998; Wang et al, 1998; Al-Hashimi et al, 2000; Prestegard et al, 2000; Zweckstetter and Bax, 2001; Lakomek et al, 2008) and/or by the preferential orientation of the molecule itself in a magnetic field due to its magnetic susceptibility anisotropy (Lohman and Maclean, 1978; Tolman et al, 1995; Zhang et al, 2003; Latham et al, 2008; Ravera et al, 2014; Musiani et al, 2014). RDCs obtained by alignment induced by an external orienting medium, herein referred to as diamagnetic RDCs (dRDC), depend on the nature of the interactions of the biomolecule with the medium.…”
Section: Introductionmentioning
confidence: 99%